Uso de contracepção por adolescentes de escolas públicas na Bahia Contraceptive use among adolescents at public schools in Brazil - Maria da Conceição Chagas de Almeida; Estela Maria Leão de Aquino; Lynne Gaffikin; Robert J Magnani (Universidade de São Paulo, 2003)
OBJETIVO: O interesse sobre o comportamento contraceptivo de adolescentes vem crescendo, especialmente pela relevância social conferida à gravidez nessa faixa etária. Assim, realizou-se estudo para investigar fatores associados ao uso de métodos anticoncepcionais entre adolescentes escolares. MÉTODOS: Estudo transversal que utilizou um questionário auto-aplicado em 4.774 alunos de ambos os sexos, entre 11 e 19 anos. Calcularam-se as prevalências de uso de contraceptivos na primeira e na última relação sexual e em ambas as situações (uso consistente). A regressão logística foi utilizada para a análise simultânea dos fatores e cálculo de medidas ajustadas. RESULTADOS: Entre 1.664 estudantes com iniciação sexual, os fatores associados positivamente ao uso consistente de contraceptivos pelos rapazes incluíram a iniciação sexual mais tardia, com parceria estável, contar com a família como fonte potencial de contraceptivos e acesso a serviços de saúde; entre as moças, ter iniciado a vida sexual há pouco tempo e ter o pai como fonte de informação sobre sexualidade, contracepção e prevenção DST/Aids. A gravidez foi relatada por 6,4% dos rapazes e 18,1% das moças, sendo sua ausência associada ao uso consistente de contraceptivos por elas (OR=3,83; 2,06-7,15). CONCLUSÕES: Os resultados confirmam a complexidade da determinação do comportamento contraceptivo entre adolescentes e a necessidade de que os programas educativos incorporem as múltiplas dimensões da questão para que tenham efetividade. OBJECTIVE: There has been a growing interest in patterns of contraceptive use among adolescents, due, in particular, to the social relevance attached to pregnancy in this age group. Therefore, the objective of the study was to investigate factors associated with the use of contraceptive methods among female and male adolescent students. METHOD: A cross-sectional study was conducted, by means of self-applied questionnaires, among 4,774 students ranging from 11 to 19 years of age. Prevalence with respect to the use of contraceptive methods during the first experience of sexual intercourse as well as the most recent one was calculated both separately, that is, for each of these events, and in conjunction as a measure of consistent use. Logistic regression was carried out for simultaneous analysis of factors associated with the use of contraceptive methods and in order to calculate adjusted measures. RESULTS: Among the 1,664 students who reported being sexually active, the factors positively associated with the consistent use of contraceptive methods among male students included a) postponing their first experience of sexual intercourse and interaction with a stable partner, b) the family as a potential supplier of contraceptive methods, and c) access to health services. On the other hand, among female students factors positively associated with the consistent use of contraceptive methods included a) recent sexual initiation, and b) having a father as their source of information regarding sexuality, contraception and STD/Aids prevention. Pregnancy was reported by 6.4% of the boys and 18.1% of the girls, its absence was associated with the consistent use of contraceptives by them (the girls) (Odds Ratio=3.83; 2.06-7.15). CONCLUSIONS: The results confirm the complexity of determining contraceptive behavior among adolescents and therefore reinforce the need to include multi-dimensional aspects of this theme in order to ensure the efficacy of sex education programs.